Comparison of the conformational dynamics of an N-glycan in implicit and explicit solvents. (December 2022) - Roy, Rajarshi; Poddar, Sayan; Kar, Parimal
Abstract: All-atom MD simulations provide the atomic details of glycan structure in solution, but extensive sampling is required for simulating the transition between rotameric states. For carbohydrate modeling, the motions of the glycosidic linkages in a glycan are often sampled well on the sub- μ s time scale. Consequently, simulations of large glycans or glycoconjugates in aqueous environments are very challenging at the atomistic level because of a huge number of water molecules, which eventually slows down the conformational sampling. An alternative to the all-atom approach is the multiscale simulation, where the glycan is in all-atom form while the solvent is treated implicitly. Here we present a comparative analysis of the implicit model with the currently used explicit model using Gaussian accelerated molecular dynamics (GaMD). Here we used a hybrid N -glycan to investigate the accuracy of the implicit solvent model. Estimating several structural parameters, namely dihedral torsional angles, puckering angles, and end-to-end distances, yields a complete classification of structural space in both solvent models. Both solvent models displayed similar conformations at the monosaccharide level, whereas minor differences were observed in the global conformation. The only major difference was observed in the inter-residue hydrogen bonds, which increased by 2-fold in the explicit solvent model. Detailed analysis of structural parameters established a balanced trade-off between the computational speed and accuracy for studying long-chain glycan molecules in an implicit solvent. Highlights: Comparative conformational dynamics of an N -glycan in explicit and implicit solvents were conducted. Gaussian accelerated molecular dynamics facilitated the conformational search for long N -Glycan molecules. Similar dihedral conformational space and puckering states were observed in both solvent models. The PCA analysis yielded four and three distinct clusters in the explicit and implicit solvent respectively.